2005 IFPRI at a glance: International Food Policy Research Institute - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
Achieving food security for all will require access to resources by the poor, better technologies for producing and distributing food supplies, more efficient and accountable governments, and timely and appropriate policies in the areas of food production, nutrition, natural resources, markets, and trade. IFPRI helps developing countries achieve these goals by providing research and analysis that can be used to consider different policy options for meeting food needs in a sustainable manner. Through its policy analyses, IFPRI directly supports developing-country policymakers, nongovernmental organizations (NGOs), and civil society in their efforts to help the poor. In addition, the Institute’s published research indirectly affects policy change through opinion leaders, donors, advisers, and media who influence national and international decisionmaking. IFPRI conducts food policy research and disseminates it through four research and outreach divisions, a communications division, and the 2020 Vision initiative. The focus of these divisions and initiatives is described in this brochure.